COVID-19 pandemic and its impact on social relationships and health. Issue 2 (19th August 2021) - Long, Emily; Patterson, Susan; Maxwell, Karen; Blake, Carolyn; Bosó Pérez, Raquel; Lewis, Ruth; McCann, Mark; Riddell, Julie; Skivington, Kathryn; Wilson-Lowe, Rachel; Mitchell, Kirstin R
Abstract : This essay examines key aspects of social relationships that were disrupted by the COVID-19 pandemic. It focuses explicitly on relational mechanisms of health and brings together theory and emerging evidence on the effects of the COVID-19 pandemic to make recommendations for future public health policy and recovery. We first provide an overview of the pandemic in the UK context, outlining the nature of the public health response. We then introduce four distinct domains of social relationships: social networks, social support, social interaction and intimacy, highlighting the mechanisms through which the pandemic and associated public health response drastically altered social interactions in each domain. Throughout the essay, the lens of health inequalities, and perspective of relationships as interconnecting elements in a broader system, is used to explore the varying impact of these disruptions. The essay concludes by providing recommendations for longer term recovery ensuring that the social relational cost of COVID-19 is adequately considered in efforts to rebuild.